Mechanotransduction-related ferroptosis: Enhancing boron neutron capture therapy efficacy in glioblastoma using a spheroid model - Lin-Sheng Yu; Jia-Jun Liu; Ming-Hung Yang; Yu-chun Lin; Chi-Shuo Chen (Molecular Therapy: Oncology)
Boron neutron capture therapy (BNCT) shows potential for the treatment of glioblastoma, the most aggressive form of primary brain tumor. Recently, ferroptosis, a cell death triggered by phospholipid peroxidation, has been identified as an important process in tumor therapy. However, the ferroptosis in BNCT has not been fully explored. To investigate ferroptosis induced by BNCT, U87 and U251 human glioblastoma cell lines were used. The results demonstrated that BNCT led to a significant 3- to 4-fold increase in lipid peroxides and caused approximately 25% cell death through ferroptosis in a three-dimensional (3D) spheroid model, which was employed to reconstruct the cell force interactions. Furthermore, BNCT promoted the upregulation of FACL4, an essential protein that triggers ferroptosis and induces oxidative stress by disrupting the endoplasmic reticulum and mitochondria, respectively. Moreover, we found that the mechanosensitive protein YAP-1, known to facilitate ferroptosis, was upregulated and redistributed within the spheroids after BNCT treatment, and the BNCT-induced ferroptosis was enhanced by 1.5-fold following the pharmacological interruption of cell force. This study represents the first demonstration of ferroptosis in BNCT and showed the influences of mechanotransduction in the regulation of ferroptosis, offering a potential strategy to enhance the efficacy of BNCT from the perspective of cell mechanics.